Habilidades blandas y la convivencia escolar en estudiantes de básica elemental de la escuela de educación básica “Arnulfo Chávez Miranda”, cantón Quevedo, periodo lectivo 2023-2024 - Chávez Rojas, Daniela Victoria (2024)
This educational development project investigates the impact of soft skills on school coexistence, in Basic Elementary students of the “Arnulfo Chávez Miranda” School, in the Quevedo canton. It is approached from a multidisciplinary approach that integrates elements of educational psychology, pedagogy and sociology. The theoretical framework is based on the understanding of soft skills as socio-emotional and behavioral competencies, which facilitate positive interaction between individuals in educational contexts. A diagnosis of the situation of the educational unit was carried out, using qualitative and quantitative methods to identify the challenges and needs related to school coexistence. In response to these results, a teacher training workshop focused on the development of soft skills was designed, developed and validated. This workshop was structured around practical activities, group discussions and individual reflections, with the aim of strengthening teachers' skills in key areas such as empathy, teamwork, effective communication and conflict resolution. To support this work, data was collected through surveys and digital interviews, which demonstrate the existing interest in both students and teachers in the use of soft skills to improve school coexistence.